Application of Probabilistic Analysis for Prediction of the Initiation of Landslide - Agus Setyo Muntohar, H.-J. Liao (2009)
Model for evaluating the failure probability of an inclined soil layer with an infinite length was developed in the present paper. Advantage of the probabilities analysis is since the model allows the uncertainties of soil properties, geology, and hydraulic properties of the slope. The main objective of the analysis is to estimate time of failure of slope by using Green-Ampt infiltration and infinite slope stability. Probability analysis is computed based on the Monte Carlo simulation method (MCSM). The model is then applied to evaluate the occurrence probability of shallow landslide-initiated debris flow in Tungmen gully located in the eastern Taiwan, which occurred a devastating debris flow in 1990. The statistical properties of hydrogeological parameters were collected and summarized. The soil parameter is assumed to be log normally distributed, while the hydraulic properties was assumed uniformly distributed. The simulation results the mean time to failure (MTTF) and standard deviation are about 14 hours and 3.2 hours respectively. The failure probability of MTTF is about 0.54 to occur at 11am on 23 June 1990. The failure rate of â€œdegree of beliefâ€ for occurrence at the estimated time is calculated 0.27.